Mama Adèle - Muñiz Cachón, Ángeles (Fundación El Pájaro Azul, 2014)
In Kinshasa, capital of the Democratic Republic of Congo, the Pájaro Azul Foundation, represented by Mama Adèle, trains a group of women who live surrounded by poverty, misery and misfortunes, but who do not lack in intelligence, spirit and the will to fight their way out of that situation.--